Analysis of ease of insertions, its attempts and time taken to insert for i-gel and cLMA in paediatric cases. - Dr. Nimish Jain; Dr. Susheela Taxak; Dr. Karampal Singh (International Journal of Medical Research and Review, 2021)
Aim: Analysis of ease of insertions, its attempts and time taken to insert for i-gel and cLMA in paediatric cases.Methods: We did a prospective, randomised single-blind study on Eighty patients of either sex belonging to American Society of Anaesthesiologists (ASA) physical status class I or II, between 6 months to 8 years of age, scheduled to undergo elective surgery for less than one and half hour duration under general anaesthesia. In this study we analysed the ease of insertion, attempts and time were taken to insert the supraglottic airway device.Results: The ease of insertion observed was easy in 39(97.5%) in the i-gel group and 35(87.5%) in cLMA group in our study. The i-gel was placed successfully in 39 out of 40 (97.5%) patients in the first attempt, and achieved 100% insertion on the second attempt. Correct positioning of cLMA in the first attempt was seen in 35 out of 40 (87.5%) patients. The remaining 5 patients (12.5%) required a second attempt. The average insertion time of cLMA (12.88 ± 1.771 seconds) was longer than the average time of insertion of i-gel (9.48 ± 1.037 seconds), and these differences were highly significant statistically (p= 0.000).Conclusion: To conclude, i-gel and cLMA is effective and safe devices for use in children. Both are easy to insert and have insignificant morbidity, however, time taken and attempts of insertions for i-gel was lesser than cLMA. Also, the ease of insertion was relatively easy for i-gel than cLMA in pediatric cases.